Tinjauan Artikel : Jamur Endofit Dari Akar Anggrek (Orchidaceae): Tinjauan Artikel : Jamur Endofit Dari Akar Anggrek (Orchidaceae) - R. Soelistijono (JURNAL ILMIAH AGRINECA, 2026)
Orchids, renowned for their beauty and diverse medicinal properties, are increasingly threatened by habitat destruction and illegal trade, driving many species to extinction. To better understand and conserve these fascinating plants, research into their symbiotic relationships with endophytic fungi (OEF) has become a major focus. This review paper examines the multifaceted roles of endophytic fungi in orchids, including seed germination, stress tolerance, secondary metabolite production, nutrient acquisition, and in vitro propagation. Orchid endophytic fungi play a crucial role in orchid growth and can enhance plant resistance to environmental stresses and pathogens. Endophytic fungi play a crucial role in facilitating orchid seed germination and growth by providing essential nutrients and enhancing stress tolerance. Furthermore, these fungi produce bioactive compounds with significant pharmaceutical potential, underscoring their importance in drug discovery. Furthermore, endophytic fungi enhance nutrient uptake and support micropropagation efforts, thus contributing to orchid conservation. Understanding the complex interactions between orchids and endophytic fungi is crucial for promoting sustainable floriculture, conserving biodiversity, and improving human well-being.